PENGARUH ANAK RANDAI TERHADAP PEMASARAN HASIL PERTANIAN SAYURAN (Kasus di Nagari Alahan Panjang Kecamatan Lembah Gumanti) - Yusri, Elda; Arifin, Zainal; Elfemi, Nilda (Pendidikan Sosiologi, 2013)
In agricultural trade vegetables in Nagari Alahan Long Valley District Gumanti require the services of middlemen called randai child. Activities undertaken kids marketing randai affect vegetable crops is in Nagari Alahan Panjang. Randai children directly involved either buy or sell the crop farmers. This study was conducted to see how the influence and child relationship with farmers and toke randai the marketing of vegetable crops is in Nagari Alahan Panjang, especially on the activities carried out by children randai to survive and benefit from his efforts. Based on the above problem definition , the research question is: " How does a child randai the marketing of vegetable farming. The purpose of this study was to determine and describe 1). Influence children against marketing of agricultural produce randai vegetables 2). To know how children randai in relationships with farmers and toke in Nagari Alahan Panjang. This study uses the theory of action proposed Tallcot Parson randai the child actor that can act as a controlling relationship with farmers and toke. This study used a qualitative approach with descriptive type of research, data collection by observation and interview. Informant selection techniques using purposive sampling technique. In order to obtain valid data , this study used data analysis techniques used are from Mathew B. Miles and A. Michael Huberman. The procedure is data reduction, data display and conclusion. Based on the results of the study concluded that children randai with his actions affect the marketing of vegetable crops in the villages Alahan length 1. Influence children against marketing of agricultural products randai vegetables " a). Influence on sales and purchases faster b). Effect on the availability of the crop farmers c). influence farmer relationships, children and toke randai closer 2. Randai child relationship with the farmers in getting merchandise a). Randai child relationship with farmers is hope 3. Relationship with the child randai toke in getting merchandise 4. Relationship between randai cjhild and its transportation, Labour Lift and Builders Weigh.